Factors Related to the Implementation of Initiation Early Breastfeeding (IMD) - Rusnawati; Mitra Asriani (Jurnal Life Birth, 2017)
Early Breastfeeding Initiation (IMD) is a program which in principle is not a mother who breastfeeds their babies but babies who suckle and can save 22% of babies who die before one month of age. But in the implementation is still low, this is caused by several factors including lack of mother's knowledge, lack of support from family and helpers labor that does not facilitate. The purpose of this study is to determine the factors relating to the implementation of Early Breastfeeding Initiation (IMD). This research uses the approach of a cross-sectional study. The sampling technique used in this study is purposive sampling with a sample of 42 people. Results from the study show that there is a relationship between knowledge, family support, and helpers labor with the implementation of Early Breastfeeding Initiation (IMD).